ANALYSIS OF HIGH SCHOOL STUDENTS’ CRITICAL AND COMPUTATIONAL THINKING SKILLS IN THERMOCHEMISTRY - Wibowo, Aries Setyo; Patonah, Siti; Novita, Mega (Universitas Tanjungpura, 2026)
Critical and computational thinking skills are two essential 21st-century competencies that are highly relevant in chemistry education, particularly in thermochemistry topics that require deep conceptual understanding and scientific reasoning. This study aims to provide an in-depth analysis of the profile of high school students’ critical and computational thinking skills in thermochemistry. A descriptive quantitative method was employed, involving 36 eleventh-grade students from SMAN 1 Kedungwuni. The instruments consisted of diagnostic tests based on Facione’s and Brennan & Resnick’s indicators, classroom observations, semi-structured interviews with teachers and students, and student perception questionnaires. The analysis revealed that students’ critical thinking skills were at a moderate level, with the highest score in interpretation (65.3%) and the lowest in evaluation (58.1%) and explanation (59.4%). Similarly, computational thinking skills were also in the moderate category, with the highest score in decomposition (63.2%) and the lowest in abstraction (57.3%). Observational and interview data indicated that learning was still dominated by conventional lecture methods with limited exploratory activities that promote higher-order thinking. However, students expressed strong motivation toward the use of more interactive learning media, such as websites or Android-based applications. In conclusion, these findings underscore the need for innovative, contextual, and technology-based learning media to enhance students’ critical and computational thinking skills and better align chemistry education with 21st-century learning demand.